Pengembangan Model Tata Bangunan dan Lingkungan DI Pulau Kecil Berbasis Mitigasi Bencana - Ishak, Rahmi Amin (FORUM BANGUNAN, 2013)
Level of vulnerability of small islands in Indonesia are high to disasters due to climate change, impact on sea level rise, increase in rainfall, and temperature rise. This affects sectors of community life in a small island, namely the settlement, economy, agriculture, tourism, etc.This paper focuses on disaster mitigation in small island viewed from the perspective of the architectural layout of the building and the environment in facing disaster risk. The impact of disasters on community can be prevented as focusing on the arrangement of the buildings and the environment, with technology engineering effort. Spatial planning for disaster mitigation conducted by adjusting the structure and patterns of space utilization with the vulnerability of the region to various forms of natural occurrence that could potentially occur.Â